Autoimmune diseases: a diagnostic challenge: Avtoimunske bolezni: diagnostični izziv - Pahor, Artur (Acta Medico-Biotechnica, 2021)
The immune system defends humans against foreign factors that could damage healthy tissue. It detects and distinguishes a wide variety of substances from the organism’s own structures. Failing to recognize the organism’s own structures as self structures causes autoimmune disorders. These self-structures are called “autoantigens”. Autoimmune disorders are divided into those directly damaging only a single organ system, and those in which many important organs are damaged (systemic). This article deals with the most important autoimmune mechanisms inducing autoimmune inflammation. It discusses the diagnoses of autoimmune disorders, which are based mainly on the clinical picture, and the most frequently used laboratory and immunological tests crucial for diagnosing particular autoimmune diseases. The purpose of this article is to emphasize the importance of the early clinical picture and laboratory testing of autoimmune diseases.
Keywords: autoimmune diseases; pathogenesis; diagnosis